Anti‐Inflammatory Effects and Prediction of Blood Pressure Response by Baseline Inflammatory State in Catheter‐Based Renal Denervation. Issue 11 (1st June 2016) - Lang, David; Nahler, Alexander; Lambert, Thomas; Grund, Michael; Kammler, Jürgen; Kellermair, Jörg; Blessberger, Hermann; Kypta, Alexander; Steinwender, Clemens; Auer, Johann
Abstract : This retrospective analysis aimed to examine off‐target effects on inflammatory and renal function parameters in n=78 subsequent patients treated with renal denervation (RDN) for resistant hypertension. Ambulatory and office blood pressure (ABP/OBP), serum creatinine, glomerular filtration rate (GFR), cystatin C, C‐reactive protein (CRP), interleukin‐6 (IL‐6), and white blood cell count (WBC) were assessed before, 6 and 12 months after RDN. ABP was significantly reduced by −8.2/−3.8 mm Hg ( P =.002/.021) at 1 year after RDN, while an initial OBP reduction was not sustained during follow‐up. IL‐6 levels significantly decreased by −0.5 pg/mL ( P =.042) and by −1.7 pg/mL ( P <.001) at 6 and 12 months, baseline IL‐6 levels possibly predicting ABP response to RDN ( r =−0.295; P =.020). Concurrently, leukocyte count was reduced by −0.5 × 10 3 /μL ( P =.017) and −0.8 × 10 3 /μL ( P <.001), respectively. Serum creatinine and GFR remained unchanged, but we observed a significant increase in cystatin C by 0.04 mg/L ( P =.026) and 0.14 mg/L ( P <.001) at 6 and 12 months after the intervention.